A New Family of Layered Metal-Organic Semiconductors: Cu/V-Organophosphonates - Tholen, Patrik; Wagner, Lukas; Ruthes, Jean G. A.; Siemensmeyer, Konrad; Beglau, Thi Hai Yen; Muth, Dominik; Zorlu, Yunus (Wiley-V C H Verlag Gmbh, 2023)
Herein, we report the design and synthesis of a layered redox-active, antiferromagnetic metal organic semiconductor crystals with the chemical formula [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] (where PPA is phenylphosphonate). The crystal structure of [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] shows that the metal phosphonate layers are separated by phenyl groups of the phenyl phosphonate linker. Tauc plotting of diffuse reflectance spectra indicates that [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] has an indirect band gap of 2.19 eV. Photoluminescence (PL) spectra indicate a complex landscape of energy states with PL peaks at 1.8 and 2.2 eV. [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] has estimated hybrid ionic and electronic conductivity values between 0.13 and 0.6 S m(-1). Temperature-dependent magnetization measurements show that [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] exhibits short range antiferromagnetic order between Cu(II) and V(IV) ions. [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] is also photoluminescent with photoluminescence quantum yield of 0.02%. [Cu(H2O)(2)V(& mu;-O)(PPA)(2)] shows high electrochemical, and thermal stability.
Keywords: layered magnetic materials; layered metal organic semiconductors; metal organic frameworks